A Review of Studies on Lateral Load Reinforcement Systems in RC Structures Frames (Journal of Civil Engineering Researchers, 2021)
Lateral load-bearing systems are part of a structure that has the task of withstanding lateral loads and directing them from asafe path to the foundation. Ancillary forces can include earthquake load, wind load, or other forces. Nowadays, with theincreasing use of concrete structures in construction projects, also the basic need to strengthen concrete structures for variousreasons such as changing the use of the building, the age of the building and other things, knowing and using new andappropriate methods for Increasing the bearing capacity of concrete building frames against lateral forces is essential andunavoidable. In this article, by reviewing new articles and researches in the field of new types of lateral load reinforcementsystems in reinforced concrete frames, the efficiency and productivity of each method have been evaluated and measured.
Keywords: Reinforcement; RC Structures Frames; Braced Concrete Frames; Lateral Load